Monitoring of synthetic insecticides resistance and mechanisms among malaria vector mosquitoes in Iran: A systematic review. Issue 1 (January 2022) - Abbasi, Ebrahim; Vahedi, Mozaffar; Bagheri, Masoumeh; Gholizadeh, Saber; Alipour, Hamzeh; Moemenbellah-Fard, Mohammad Djaefar
Abstract: Background: In Iran, the prospect of malaria control relies mainly on insecticides used against the genus Anopheles (Diptera: Culicidae) as important vectors of malaria, arboviruses, and so on. Only eight out of 30 malaria mosquito vectors ( Anopheles species) have been examined for insecticide resistance in Iran. This study aimed to review articles related to the incremental trend in insecticide resistance and their mechanisms among anopheline malaria vectors in Iran. Methods: A literature review was conducted based on such search engines as Iran doc, Web of Science, SID, PubMed, Scopus, and Google Scholar websites using the following keywords: " Anopheles, " "Malaria, " "Resistance, " "Vectors, " "Insecticide Resistance, " and "Iran" for data collection. Published papers in English or Persian covering 1980 to 2020 were reviewed. Results: A total of 1125 articles were screened, only 16 of which were filtered to be pertinent in this review. While most of the mosquito vectors of malaria, such as Anopheles stephensi, were resistant to DDT, dieldrin, malathion, and becoming less susceptible to deltamethrin and other synthetic pyrethroid insecticides, few like Anopheles fluviatilis s. l. were susceptible to all insecticides. A disseminating trend in insecticide resistance among different anopheline mosquito vector species was evident. Metabolic and insecticide target-site resistance mechanisms were involved with organochlorines and pyrethroids, respectively. Conclusions: Insecticide resistance is becoming a severe scourge to the effectiveness of vector-borne disease management measures. This event is especially critical in developing and marginalized communities that applied chemical-based vector elimination programs for malaria; therefore, it is crucial to monitor insecticide resistance in malaria vectors in Iran using biochemical and molecular tools. Abstract : Anophelinae, Carbamate, Knock-down resistance, Organophosphate, Pyrethrum.